2021
DOI: 10.3389/fmicb.2021.703560
|View full text |Cite
|
Sign up to set email alerts
|

Secrets of the Hospital Underbelly: Patterns of Abundance of Antimicrobial Resistance Genes in Hospital Wastewater Vary by Specific Antimicrobial and Bacterial Family

Abstract: Background: Hospital wastewater is a major source of antimicrobial resistance (AMR) outflow into the environment. This study uses metagenomics to study how hospital clinical activity impacts antimicrobial resistance genes (ARGs) abundances in hospital wastewater.Methods: Sewage was collected over a 24-h period from multiple wastewater collection points (CPs) representing different specialties within a tertiary hospital site and simultaneously from community sewage works. High throughput shotgun sequencing was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 52 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…Healthcare settings such as hospitals and nursing homes can act as point sources of contamination of municipal sewerage systems with ARB and ARGs ( Rodriguez-mozaz et al, 2014 ; Khan et al, 2019 ; Perry et al, 2021 ). Greater quantities and different classes of antibiotics are being used in healthcare settings when compared to communities ( ECDC, 2020 ).…”
Section: Conceptual and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare settings such as hospitals and nursing homes can act as point sources of contamination of municipal sewerage systems with ARB and ARGs ( Rodriguez-mozaz et al, 2014 ; Khan et al, 2019 ; Perry et al, 2021 ). Greater quantities and different classes of antibiotics are being used in healthcare settings when compared to communities ( ECDC, 2020 ).…”
Section: Conceptual and Theoretical Frameworkmentioning
confidence: 99%
“…Hospital clinical reported data can be a source of reliable reference information for comparing with the WWS finding, but as mentioned earlier, hospital data represents only a fraction of the problem. Hospital wastewater is considered the next option, but also includes relatively more ARB from clinical isolates ( Perry et al, 2019 , 2021 ; Majlander et al, 2021 ; Hutinel et al, 2022 ). In addition, the geographical region of the sewerage network and hospital coverage area may not necessarily overlap ( Karkman et al, 2020 ; Tiwari et al, 2022d ).…”
Section: Limitations Of Wastewater Surveillance and Future Directionmentioning
confidence: 99%
“…Perry et al compared sewage samples from a hospital and the surrounding community sewage plants. The authors modeled the correlation between antimicrobial usage in the hospital and resistance gene abundances and showed that sewage from the hospital has a higher percentage of Antibiotic Resistance Genes (ARGs) compared to the communal sewage samples [ 136 ]. Another interesting function to study would be the microbial association network from microbiome data in order to capture the interactions between the various identified species.…”
Section: Focus On Bacterial Communitiesmentioning
confidence: 99%
“…This, coupled with open drainage systems and inefficient wastewater treatment plants, can lead to the dissemination of HWW contents, including antimicrobial residues and MDR pathogens, into the local environment and community ( 9 ). Metagenomic surveillance of HWW using short-read next-generation sequencing data is an efficient approach for assessing the overall AMR burden in a given hospital ( 10 12 ). Unlike traditional culture- and PCR-based approaches, which are laborious and limited to selected taxa and ARGs, metagenomics can quantify thousands of species, ARGs, and virulence factors (VFs) from a single sample at a relatively low cost.…”
Section: Introductionmentioning
confidence: 99%